Evaluating the Role of Lecturer Knowledge and Personal Initiative in Improving Learning Outcomes and Graduate Quality in Higher Education Institutions: A PLS-SEM Analysis - Irfansyah, Ade; Suparji, Suparji; Suprianto, Bambang (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to evaluate the influence of lecturer knowledge and personal initiative on improving learning outcomes and graduate quality in higher education institutions. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), this study examines the relationships between these variables based on data collected from faculty members and student performance records over a 12-month period. The analysis reveals a significant positive effect of both lecturer knowledge and personal initiative on student learning outcomes and the overall quality of graduates. These findings suggest that targeted faculty development programs can play a critical role in enhancing educational quality and institutional reputation.